Storia dei filosofi - Philodemus, approximately 110-approximately 40 B.C. (Philosophia Antiqua, 1994)
The Stoicorum historia ( PHerc. 1018) is one book in Philodemus' extensive History of Philosophy . The Epicurean philosopher Philodemus wrote this work during a stay in Italy circa 70-60 B.C. with the aim of offering learned Romans an objective and unpolemical history of the Greek philosophical schools. Philodemus sketches the lives and times of the main representatives of Stoicism from Zeno of Citium to Panaetius of Rhodes. The Stoicorum historia hands down a mass of information on the lives and thought of the Stoics which is not found in Diogenes Laertius' Lives of Eminent Philosophers (Book VII). This new edition contains the text of PHerc. 1018, now revised, on a critical basis, and Italian translation and commentary. An introduction and indexes complete the work.